Research Developments in World Englishes - Onysko, Alexander (Bloomsbury Advances in World Englishes, 2021)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. It is funded by the University of Klagenfurt, Austria. Discussing key issues of current relevance and setting the tone for future research in world Englishes, this book provides new perspectives on the diverse realities of Englishes around the world. Written by an international team of established and renowned scholars, it is the inaugural volume in the new series Bloomsbury Advances in World Englishes, dedicated to advancing research in the field. Chapters discuss important topics in contemporary world Englishes research, including de-colonial approaches, emerging varieties in post-protectorates and international uses as communicative events to highlight the globalizing aspect of English as a semiotic code. The book also expands on cultural conceptualizations to investigate the connections between Englishes and localized cultural knowledge and ongoing changes and attitudes towards local forms in multilingual settings. Closing with an examination of how world Englishes and the use of English as a lingua franca could influence the future teaching of Englishes, Research Developments in World Englishes presents a detailed picture of contemporary research approaches and points the way towards exciting future directions.